2020
DOI: 10.1186/s13000-019-0912-3
|View full text |Cite
|
Sign up to set email alerts
|

The role of CD68+ macrophage in classical Hodgkin lymphoma patients from Egypt

Abstract: Background: CD68+ tumor-associated macrophages (TAM) play an important role in the progression of classical Hodgkin lymphoma (cHL). We assessed the role of CD20 and CD68 + TAM in a cohort of cHL patients from Egypt and correlated the number of CD68 + cells with patients' characteristics, response to treatment, overall and progression free survival rates (OS & PFS). Methods: CD20 expression and CD68 + TAM numbers were assessed in representative tumor tissues obtained from 81 cHL patients using flowcytometry (FC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 31 publications
0
7
0
1
Order By: Relevance
“…These macrophages could be considered as “bad guys”, with a pro-tumor activity and a possible inhibition of drug-mediated cell death, leading to a reduced treatment response, disease progression and reduced survival [ 115 ]. Since then, many subsequent reports were published, but showed conflicting results about a definitive association between TAM and survival, as illustrated in Table 1 [ 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 ].…”
Section: Tam In Hodgkin Lymphomamentioning
confidence: 99%
See 1 more Smart Citation
“…These macrophages could be considered as “bad guys”, with a pro-tumor activity and a possible inhibition of drug-mediated cell death, leading to a reduced treatment response, disease progression and reduced survival [ 115 ]. Since then, many subsequent reports were published, but showed conflicting results about a definitive association between TAM and survival, as illustrated in Table 1 [ 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 ].…”
Section: Tam In Hodgkin Lymphomamentioning
confidence: 99%
“…Azambuja and colleagues showed a lack of IHC reproducibility compared to GEP, while other reports suggested CD163 could represent a more appropriate marker to detect TAM infiltration compared to CD68, that could stain myelomonocytic cells, fibroblasts and endothelial cells [ 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 ].…”
Section: Tam In Hodgkin Lymphomamentioning
confidence: 99%
“…Subsequently, many studies have confirmed the association of TAMs with poor prognosis of adult HL patients (Table 1). 21‐24 A couple of studies investigated the impact of TAMs on prognosis of pediatric patients. In contrast to adult HL patients, TAMs failed to predict disease outcome in pediatric patients 8,25,26 .…”
Section: Tme Modulatorsmentioning
confidence: 99%
“…Повышение доли клеток, экспрессирующих CD163, коррелирует с вероятностью развития рецидивов заболевания и низкой общей вы живаемостью пациентов, что частично совпадает с ре зультатами зарубежных исследований, которые носят преимущественно описательный характер [9,[14][15][16]. Значимость CD68 как маркерапредиктора течения кЛХ в настоящее время доказана не в полной мере, хотя встречаются отдельные работы, в которых отра жена важная роль данного маркера [16,17].…”
Section: теоретические аспекты и фундаментальные исследования -в практику врача-онкологаunclassified